0% found this document useful (0 votes)
41 views

Chapter 4

The document discusses methods of proofs in mathematics, including direct proofs, indirect proofs (proofs by contradiction and contrapositive proofs), and examples of applying these methods. Direct proofs involve stating implications between statements to show that if P is true, then Q is true. Indirect proofs assume the conclusion Q is false and show this leads to a contradiction. Contrapositive proofs prove the contrapositive statement instead of the original statement. Examples demonstrate applying these proof techniques to statements involving inequalities, even/odd integers, and equations.

Uploaded by

Potatoprys
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
41 views

Chapter 4

The document discusses methods of proofs in mathematics, including direct proofs, indirect proofs (proofs by contradiction and contrapositive proofs), and examples of applying these methods. Direct proofs involve stating implications between statements to show that if P is true, then Q is true. Indirect proofs assume the conclusion Q is false and show this leads to a contradiction. Contrapositive proofs prove the contrapositive statement instead of the original statement. Examples demonstrate applying these proof techniques to statements involving inequalities, even/odd integers, and equations.

Uploaded by

Potatoprys
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
You are on page 1/ 9

CHAPTER 4

METHODS OF PROOFS

4.1 Direct Proof


Let P and Q be statements and consider the statement P ⇒ Q. The construction
of the direct proof of the implication P ⇒ Q involves the figuration of statements
R1 , R2 ,..., Rn , construction and arrangement of the implications

P ⇒ R1 , R1 ⇒ R2 , ..., Rn−1 ⇒ Rn , Rn ⇒ Q

By the Law of Syllogism, if all the above implications are true, then P ⇒ Q is true.

Note that the construction of a direct proof is not easy, it may involve
observation, intuition, practice, skill, patience, effort, experience, etc.
Sometimes it requires LUCK.

Summary of the Method:

Prove: P ⇒ Q
Proof : Let P . Then R1 . Thus, R2 . Hence, R3 . Therefore, Q. 

In the above summary, we have the arrangements of implications

P ⇒ R1 , R1 ⇒ R2 , R2 ⇒ R3 , R3 ⇒ Q

By the Law of Syllogism, if all the above implications are true, then P ⇒ Q is true.

Let us consider basic definitions which are very familiar. We will apply these
definitions to some of the examples.

A definition is a double implication statement but it is usually written in an


implication form. Since a definition is a double implication, it consists of four
implication statements.

Definition 4.1.1 Let a, b ∈ R. Then a > b if a − b is positive.

Restatement : Let a, b ∈ R. Then a > b if and only if a − b is positive.

Below are the four implication statements of Definition 4.1.1:

(1) Let a, b ∈ R. If a > b, then a − b is positive.


(2) Let a, b ∈ R. If a − b is positive, then a > b.
(3) Let a, b ∈ R. If a 6> b, then a − b is not positive.
(4) Let a, b ∈ R. If a − b is not positive, then a 6> b.

1
Theorem 4.1.2 Let a, b, c, d ∈ R.
1. If a > b and b > c, then a > c.
2. If a > b, then a + c > b + c.
3. If a > b and c > d, then a + c > b + d.
4. If a > b and c is positive, then ac > bc.
5. If a > b and c is negative, then bc > ac.

Let us now prove some of these properties using Definition 4.1.1.

In the first example, we apply the property: the sum of two positive real numbers
is positive.

Example 4.1.3 Let a, b, c ∈ R. Prove that if a > b and b > c, then a > c.

Proof : Let a > b and b > c. Then a − b is positive and b − c is positive. Thus,
(a − b) + (b − c) is positive. Hence, a − c is positive. Therefore, a > c. 

In the next example, we apply the trick: a − b = a + 0 − b = a + (c − c) − b =


(a + c) − (b + c).

Example 4.1.4 Let a, b, c ∈ R. Prove that if a > b, then a + c > b + c.

Proof : Let a > b. Then a − b is positive. Thus, a + c − c − b is positive. Hence,


(a + c) − (b + c) is positive. Therefore, a + c > b + c. 

The next example is similar to Example 4.1.3. Take note the following:
(a − b) + (c − d) = a − b + c − d = a + c − b − d = (a + c) − (b + d).

Example 4.1.5 Let a, b, c ∈ R. Prove that if a > b and c > d, then a + c > b + d.

Proof : Let a > b and c > d. Then a − b and c − d are positive. Thus, (a − b) + (c − d)
is positive. Hence, (a + c) − (b + d) is positive. Therefore, a + c > b + d. 

In the next example, apply the property: the product of two positive real numbers
is positive.

Example 4.1.6 Let a, b, c ∈ R. Prove that if a > b and c is positive, then ac > bc.

Proof : Let a > b and c is positive. Then a − b is positive and c is positive. Thus,
(a − b)c is positive. Hence, ac − bc is positive. Therefore, ac > bc. 

Example 4.1.7 Let a, b, c ∈ R. Prove that if a > b and c is negative, then bc > ac.

2
Proof : Let a > b and c is negative. Then a − b is positive and −c is positive. Thus,
(a − b)(−c) is positive. Hence, bc − ac is positive. Therefore, bc > ac. 

Definition 4.1.8 Let m be an integer. Then m is even if there exists an integer k


such that m = 2k.
Restatement: Let m be an integer. Then m is even if and only if ∃ k ∈ Z such
that m = 2k.

Definition 4.1.9 Let n be an integer. Then n is odd if there exists an integer t such
that n = 2t + 1.
Restatement: Let n be an integer. Then n is odd if and only if ∃ t ∈ Z such that
n = 2t + 1.

Example 4.1.10 Prove: If m is an even integer, then m2 + 2 is an even integer.

Proof : Let m be an even integer. Then ∃ k ∈ Z such that m = 2k. Thus,


m2 + 2 = (2k)2 + 2 = 4k 2 + 2 = 2(2k 2 + 1).
Let p = 2k 2 + 1 ∈ Z. Hence, ∃ p ∈ Z such that m2 + 2 = 2p. Therefore, m2 + 2 is
even. 

Example 4.1.11 Prove: If n is an odd integer, then n2 + 3 is even.

Proof : Let n be an odd integer. Then ∃ t ∈ Z such that n = 2t + 1. Thus,


n2 + 3 = (2t + 1)2 + 3 = 4t2 + 4t + 1 + 3 = 4t2 + 4t + 4 = 2(2t2 + 2t + 2).
Let p = 2t2 + 2t + 2 ∈ Z. Hence, ∃ p ∈ Z such that n2 + 3 = 2p. Therefore, n2 + 3 is
even. 

Example 4.1.12 Prove: If n is an odd integer, then n3 + −2n is odd.

Proof : Let n be an odd integer. Then ∃ t ∈ Z such that n = 2t + 1. Thus,


n3 − 2n = (2t + 1)3 − 2(2t + 1)
= 8t3 + 12t2 + 6t + 1 − 4t − 2
= 8t3 + 12t2 + 2t − 1
= 8t3 + 12t2 + 2t − 2 + 1
= 2(4t3 + 6t2 + t − 1) + 1.
Let p = 4t3 + 6t2 + t − 1 ∈ Z. Hence, ∃ p ∈ Z such that n3 − 2n = 2p + 1. Therefore,
n3 − 2n is odd. 

Example 4.1.13 Let m, n ∈ Z. Prove that if m is even and n is odd, then mn + 3


is odd.

Proof : Let m be even and n be odd. Then ∃ k ∈ Z such that m = 2k and ∃ t ∈ Z


such that n = 2t + 1. Thus,

3
mn + 3 = (2k)(2t + 1) + 3 = 4kt + 2k + +3 = 4kt + 2k + 2 + 1 = 2(2kt + k + 1) + 1.

Let p = 2kt + k + 1 ∈ Z. Hence, ∃ p ∈ Z such that mn + 3 = 2p + 1. Therefore,


mn + 3 is odd. 

Example 4.1.14 Let m, n ∈ Z. Prove that if m is even and n is odd, then


m2 + mn + n2 is odd.

Proof : Let m be even and n be odd. Then ∃ k, t ∈ Z such that m = 2k and n = 2t+1.
Thus,

m2 + mn + n2 = (2k)2 + (2k)(2t + 1) + (2t + 1)2


= 4k 2 + 4kt + 2k + 4t2 + 4t + 1
= 2(2k 2 + 2kt + k + 2t2 + 2t) + 1.

Let p = 2k 2 + 2kt + k + 2t2 + 2t ∈ Z. Hence, ∃ p ∈ Z such that m2 + mn + n2 = 2p + 1.


Therefore, m2 + mn + n2 is odd. 

4.2 Indirect Proof


There are two types of indirect proofs, the proof by contradiction and the
contrapositive proof. The most important part of these proofs is the assumption
that the comclusion Q is false or the statement ∼ Q is true.

Proof by Contradiction

This method of proof apply the following technique. If R is a contradiction


statement, then the two statements

(P ∧ ∼ Q) ⇒ R and P ⇒ Q

are logically equivalent. Hence, to prove that P ⇒ Q, we show that (P ∧ ∼ Q)


implies a contradiction.

Summary of the Method:

Prove: P ⇒ Q
Proof : Let P . Suppose ∼ Q. Then R1 . Thus, R2 ... Hence, Rn . This is a
contradiction to... Therefore, Q. 

Theorem 4.2.1 Let a ∈ R.


1. If a > 0, then a1 > 0.
2. If a < 0, then a1 < 0.

1
Example 4.2.2 Let a ∈ R. Prove that if a > 0, then a
> 0.

4
Proof : Let a > 0. Suppose that a1 ≯ 0. Then a1 ≤ 0. Thus, a( a1 ) ≤ a(0). Hence,
1 ≤ 0. This is a contradiction to the fact that 1 > 0. Therefore, a1 > 0. 

1
Example 4.2.3 Let a ∈ R. Prove that if a < 0, then a
< 0.

Proof : Let a < 0. Suppose that a1 ≮ 0. Then a1 ≥ 0. Thus, a( a1 ) ≤ a(0). Hence,


1 ≤ 0. This is a contradiction to the fact that 1 > 0. Therefore, a1 < 0. 
1
Note that in the above proof: since a < 0 and a
≥ 0, applying Theorem 4.1.2(5),
we get a( a1 ) ≤ a(0).

Definition 4.2.4 Let X and Y be sets. Then X ⊆ Y if ∀ x ∈ X, x ∈ Y .

Example 4.2.5 Prove that the empty set is a subset of every set.

Restatement: If A is any set, then ∅ ⊆ A.

Proof : Let A be any set. Suppose that ∅ * A. Then ∃ x ∈ ∅ such that x ∈


/ A. This
contradicts the fact that ∅ has no element. Therefore, ∅ ⊆ A. 

Theorem 4.2.6 (Trichotomy Property) If a ∈ R, then exactly one of the following


holds:

a > 0, a = 0, a < 0.

Example 4.2.7 Let a, b ∈ R. Use the Trichotomy Property to prove that if a ≤ b


and a ≥ b, then a = b.

Proof : Let a ≤ b and a ≥ b. Suppose that a 6= b. Then a − b 6= 0. By the Trichotomy


Property, a − b > 0 or a − b < 0. Hence, a > b or a < b. This contradicts the
hypothesis. Therefore, a = b. 

Theorem 4.2.8 Let a ∈ R. If a 6= 0, then a2 > 0.

Example 4.2.9 Let a, b ∈ R. Prove that if a2 + b2 = 0, then a = 0 and b = 0.

Proof : Let a2 + b2 = 0. Suppose that a 6= 0 or b 6= 0. By Theorem 4.2.8, a2 > 0 or


b2 > 0. Hence, a2 + b2 > 0. This contradicts the hypothesis. Therefore, a = 0 and
b = 0. 

5
Contrapositive Proof

Summary of the Method:

Prove: P ⇒ Q
Proof (Contrapositive): Let ∼ Q. Then R1 . Thus, R2 ... Hence, Rn . Therefore, ∼ P .


To prove the statement P ⇒ Q using the contapositive proof is to prove its


contrapositive ∼ Q ⇒∼ P . Thus, it is important to know the contrapositive of an
implication statement.

Example 4.2.10 Let a, b ∈ R. Use the Trichotomy Property to prove that if a ≤ b


and a ≥ b, then a = b.

Proof (Contrapositive): Let a 6= b. Then a − b 6= 0. By the Trichotomy Property,


a − b > 0 or a − b < 0. Hence, a > b or a < b. 

Note that the contrapositive of the statement to prove is ”Let a, b ∈ R. If a 6= b,


then a > b or a < b”.

Example 4.2.11 Let a, b ∈ R. Prove that if a2 + b2 = 0, then a = 0 and b = 0.

Proof (Contrapositive): Let a 6= 0 or b 6= 0. By Theorem 4.2.8, a2 > 0 or b2 > 0.


Thus, a2 + b2 > 0. Hence, a2 + b2 6= 0. 

Note that the contrapositive of the statement to prove is ”Let a, b ∈ R. If a 6= 0


or b 6= 0, then a2 + b2 6= 0”.

4.3 Mathematical Induction


Theorem 4.3.1 (Principle of Well-Ordering) Every nonempty subset of the set
of positive integers has a smallest elemant, that is, if S ⊆ Z+ and S 6= ∅, then there
exists x0 ∈ S such that x0 ≤ x for all x ∈ S.

Theorem 4.3.2 (Principle of Mathematical Induction) Let S be a subset of N


that possesses the properties:
(1) 1 ∈ S;
(2) if k ∈ S, then k + 1 ∈ S.
Then S = N.

Theorem 4.3.3 (Principle of Mathematical Induction, Version 2) For each


n ∈ N, let P (n) be a statement about n. Suppose that:
(1) P (1) is true;
(2) if P (k) is true, then P (k + 1) is true.
Then P (n) is true for all n ∈ N.

6
n(n + 1)
Example 4.3.4 Prove: ∀ n ∈ N, 1 + 2 + 3 + ... + n = .
2
n(n + 1)
Proof : Let P (n) be 1 + 2 + 3 + ... + n = .
2
1(1 + 1)
(1) Let n = 1. Then 1 = . Thus, 1 = 1. Hence, P (1) is true.
2
k(k + 1)
(2) Let P (k) be true. Then 1 + 2 + 3 + ... + k = . Thus,
2
k(k + 1)
1 + 2 + 3 + ... + k + (k + 1) = + (k + 1)
2
k(k + 1) + 2(k + 1)
=
2
(k + 1)(k + 2)
= .
2
Hence, P (k + 1) is true.

n(n + 1)
Therefore, ∀ n ∈ N, 1 + 2 + 3 + ... + n = .
2

1 − rn+1
Example 4.3.5 Let r ∈ R, r 6= 1. Prove: ∀ n ∈ N, 1 + r + r2 + ... + rn = .
1−r
1 − rn+1
Proof : Let P (n) be 1 + r + r2 + ... + rn = .
1−r
1 − r1+1
(1) Let n = 1. Then 1 + r = . Thus, 1 + r = 1 + r. Hence, P (1) is true.
1−r
1 − rk+1
(2) Let P (k) be true. Then 1 + r + r2 + ... + rk = . Thus,
1−r
1 − rk+1
1 + r + r2 + ... + rk + rk+1 = + rk+1
1−r
1 − rk+1 + rk+1 − rk+2
=
1−r
1 − rk+2
= .
1−r
Hence, P (k + 1) is true.

1 − rn+1
Therefore, ∀ n ∈ N, 1 + r + r2 + ... + rn = .
1−r

Example 4.3.6 Prove: ∀ n ∈ N, n < 2n .

Proof : Let P (n) be n < 2n .

(1) Let n = 1. Then 1 < 21 . Hence, P (1) is true.

7
(2) Let P (k) be true. Then k < 2k . Thus,

k + 1 < 2k + 1
< 2k + 2k , (1 < 2k )
= 2k · 2
= 2k+1 .

Hence, P (k + 1) is true.

Therefore, ∀ n ∈ N, n < 2n . 

Example 4.3.7 Prove: ∀ n ≥ 4, n ∈ N, 2n < n!.

Proof : Let P (n) be 2n < n!.

(1) Let n = 4. Then 24 < 4!. Thus, 16 < 24. Hence, P (4) is true.

(2) ∀k ≥ 4, let P (k) be true. Then 2k < k!. Thus,

2k+1 = 2k + 2k
< k! + k!
< k · k! + k!
= (k + 1)k!
= (k + 1)!.

Hence, P (k + 1) is true.

Therefore, ∀ n ≥ 4, n ∈ N, 2n < n!. 

Example 4.3.8 Prove: ∀ n ∈ N, 9n − 1 is divisible by 8.

Proof : Let P (n) be 9n − 1 is divisible by 8.

(1) Let n = 1. Then 91 − 1 = 8 is divisible by 8. Hence, P (1) is true.

(2) Let P (k) be true. Then 9k − 1 is divisible by 8. Thus,

9k+1 − 1 = 9 · 9k − 9k + 9k − 1
= 8 · 9k + (9k − 1).

Since 8 · 9k and 9k − 1 are divisible by 8, it follows that 8 · 9k + (9k − 1) is divisible


by 8. Thus, 9k+1 − 1 is divisible by 8. Hence, P (k + 1) is true.

Therefore, ∀ n ∈ N, 9n − 1 is divisible by 8. 

8
Exercises

I. Prove the following statements.


1. If m is an even integer, then 3m + 1 is odd.
2. If n is an odd integer, then (n + 1)2 is even.
3. If m is an even integer, then n3 + n + 4 is even.
4. Let m and n be integers. If m is even and n is odd, then (m + n)2 is odd.
5. Let m and n be integers. If m is even and n is odd, then m2 + n2 + 3 is even.

II. Prove the following statements.


1. Let a, b ∈ R. Then a2 + b2 = 0 if and√only if a = 0 and b = 0.
2. Let a, b ∈ R. If 0 < a < b, then a < ab < b and 0 < 1b < a1 .
3. Let a, b, c, d ∈ R. If 0 < a < b and 0 < c < d, then 0 < ac < bd.
4. Let a, b, c, d ∈ R. If a < b and c < d, then ad + bc < ac + bd.
5. Let c ∈ R. If 0 < c < 1, then 0 < c2 < c < 1.

III. Prove the following statements by Mathematical Induction.


n
1. ∀ n ∈ N, 1 + 3 + 32 + 33 + ... + 3n−1 = 3 2−1 .
2 2
2. ∀ n ∈ N, 13 + 23 + 33 + ... + n3 = n (n+1)
4
.
3n(n+1)
3. ∀ n ∈ N, 3 + 6 + 9 + ... + 3n = 2
.
2
4. ∀ n ∈ N, n + 3n is divisible by 2.
5. ∀ n ∈ N, 52n − 1 is divisible by 8.
6. ∀ n ∈ N, 3 is a factor of n2 − n.
7. ∀ n ≥ 7, n ∈ N, 3n < n!.
8. ∀ n ≥ 5, n ∈ N, 2n − 3 < 2n−2 .
9. ∀ n ≥ 5, n ∈ N, n2 < 2n .
10. ∀ n ∈ N, n2 ≥ n.

You might also like